ANALYZING BROAD MONEY DYNAMICS IN NIGERIA: EVIDENCE FROM ARDL BOUNDS TEST (1995–2018) - Obinna , Amadi Chukwuma; Okorie, Uchenna Emmanuel (Ayden International Journal of Basic and Applied Sciences, 2025)
The present study model determinant of broad money in Nigeria between 1995 to 2018 using auto regressive distributed lag (ALDL) Bound test techniques. In an attempt to achieve the desire results the study target were to establish a suitable ARDL model in modeling Broad money in Nigeria, to examine the long-run relationship between broad money with its determinants and to compare the performers of ARDL models on the basic of their Akaike and Schwarz information criteria. Therefore, two research questions and hypotheses will set to guides the study. The data for the study conserved between 1995 to 2018 and it was extracted from the Central Bank of Nigeria (CBN) online statistical billion. The data prints for the study was nine hundred and seventy two (828). The data for the study were analysed using Econometric view software (Eviews) version ten. The results revealed that there is both theoretical and prove implication for the direction of the interaction between broad money and it’s determinants. Also it was found that in the long-run the speed of adjustment was – 1.093 which is an indication that about 109.3% of any movements into disequilibrium between broad money and its determinants are corrected with one month. In like manner, the result shows that there is an interaction between broad money and its determinants. Sequel to the above findings recommendations were made in the study for decision and policy making